Propylthiouracil (PTU)-induced hypothyroidism alleviates burn-induced multiple organ injury - VELİOĞLU ÖĞÜNÇ, AYLİZ; YEGEN, BERRAK; ERCAN, FERİHA (ELSEVIER SCI LTD, 2006)
Oxidative stress has an important role in the development of multiorgan failure after major burn. This study was designed to determine the possible protective effect of experimental hypothyroidism in hepatic and gastrointestinal injury induced by thermal trauma. Sprague Dawley rats were administered saline or PTU (10 mg kg(-1) i.p.) for 15 days, and hypothyroidism was confirmed by depressed serum T-3 and T-4 concentrations. Under brief ether anesthesia, shaved dorsurn of rats was exposed to 90 degrees C (burn group) or 25 degrees C (control group) water bath for 10 s. PTU or saline treatment was repeated at the 12th hour of the burn. Rats were decapitated 24 h after injury and tissue samples from liver, stomach and ileum were taken for the determination of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen contents. Formation of reactive oxygen species in tissue samples was monitored by using chemiluminescence (CL) technique with luminol and lucigenin probes. Tissues were also examined microscopically. Tumor necrosis factor (TNF)-alpha and lactate dehydrogenase (LDH) were assayed in serum samples. Severe skin scald injury (30% of. total body surface area) caused a significant decrease in GSH level, which was accompanied with significant increases in NIDA level, MPO activity, CL levels and collagen content of the studied tissues (p < 0.05-0.001). Similarly, serum TNF-alpha and LDH were elevated in the burn group as compared to control group. On the other hand, PTU treatment reversed all these biochemical indices, as well as histopathological alterations induced by thermal trauma. Our results suggest that PTU-induced hypothyroidism reduces oxidative damage in the hepatic, gastric and ileal tissues probably due to hypometabolism, which is associated with decreased production of reactive oxygen metabolites and enhancement of antioxidant mechanisms. (C) 2006 Elsevier Ltd and ISBI. All rights reserved.
Keywords: PTU; experimental hypothyroidism; GSH; MPO; lipid peroxidation; LIPID-PEROXIDATION; OXIDATIVE STRESS; THERMAL-INJURY; FREE-RADICALS; LIVER-MITOCHONDRIA; ANTITHYROID DRUGS; REACTIVE OXYGEN; THYROID STATUS; RAT; MECHANISMS